Stochastic Model for Assessing the Availability of Smart Hospitals - Rodrigues, Laécio; Gonçalves, Igor; Fé, Iure; Endo, Patrícia; Silva, Francisco Airton (Proceedings of the Workshop on Performance of Computer and Communication Systems (WPerformance), 2020)
Smart hospitals need local and remote servers to efficiently process and store data. However, there is a significant difficulty in assessing the availability of such systems in real contexts, because failures are not tolerated and the cost of prototyping is high. This paper adopts Stochastic Petri Nets (SPNs) to assess the availability of an smart hospital system, avoiding premature investment in real equipment. In addition, this work presents a sensitivity analysis that identifies the most critical architecture components. The proposed model has the potential to assist hospital systems administrators in planning more optimized architectures according to their needs.